The Concept Of Faith And Disbelief In Arabic And English Literature, The Poem Of English Poet Percy Shelly’s”The Revolt Of Islam”, Literary And Doctrinal Study - Al-Saffar, RehabNadhir; Hassan Saleh, Aati (Opción, 2019)
The study highlights on the main concepts of the belief and disbelief on one hand and the literary and doctrinal study of the Percy Shelly’s poem “The Revolt of Islam” on the other hand. It is clear that, in the first section, the study will not put remedies for all the problems of the Islamic community, but it will limit its atten- tion to the concept of belief and disbelief and the subject of Takfir which imported from the wrong understanding of the concept of belief. The study will deal with two major topics in two sections: The first section is to study the subject of faith, disbelief and their definitions and meanings, as well as it will include the issue of Takfir ( extremism) which is one of the most serious contemporary challenges of the nation. The subject of Takfir (extremism) and bloodshed and its interference in the depth of the civilizational struggle of the nation play an important side of this study. It is one of the most serious issues that we are suffering from. It is clear that the first section reinforced by evidence from the book (Qura’an) and purified Sunnah. On the other hand section two concentrates on the main tendencies of the poem “The revolt of Islam” by the English poet Percy Shelly. It represents the rev- olution of Islam against unjust and tyranny. The poet had used the “The revolt of Islam “ to be the title of one of his great works, even though some critics believes that he want to hide his thoughts and ideology. The poem reflects the believing side of the poet, also he understand Islam as a tolerant religion and believing in its in- structions. According to Shelly’s concept, the mad world needs a clear revolts like this one. In the beginning of this section, the study concentrates on the main char- acters of this long poem, the main plot, and the main themes and motifs in a brief introduction. In the second part of the chapter, the study goes forward of critics’ interpretations and debates on Shelly’s poem “The Revolt of Islam” The poet was famous of his atheistic thoughts, and it for some critics, represents a paradoxical matter. The last paragraph shows how the Islamic concepts particularly influenced the writer himself and influenced the English literature in general.